IMPLEMENTASI PENGELOLAAN KEUANGAN PELAKU UMKM BERDASARKAN SAK-EMKM - Afif, Ali (Jurnal Akuntansi, Auditing dan Investasi, 2021)
This research was conducted on SMEs to analyze financial management. The results of financial management play a role in knowing the right steps for MSME actors to manage their business. This research method uses a qualitative form, namely by explaining various phenomena experienced by researchers from various literature sources. The limitations in this research approach are in every report that has been made by MSME actors, after that the researcher explains various theories and then prepares financial statements based on SAK EMKM. Based on the results of the research that has been carried out along with the descriptions that have been put forward regarding the discussion of financial statement analysis of MSME business actors, it can be concluded that MSME business actors have not been able to compile financial reports based on SAK EMKM. This can be seen from the evidence of the data that the researcher received, which is only in the form of recording the entry and exit of cash, recording the number of sales and purchases, and records of costs incurred. The inability of MSME actors in compiling financial reports based on SAK EMKM is due to a lack of information and processes as well as socialization in financial management.